Development of a method for the synthesis of 2,4,5-trisubstituted oxazoles composed of carboxylic acid, amino acid, and boronic acid - Yamada, Kohei; Kamimura, Naoto; Kunishima, Munetaka (Beilstein Journal of Organic Chemistry, 2017)
A novel method for the synthesis of trisubstituted oxazoles via a one-pot oxazole synthesis/Suzuki–Miyaura coupling sequence has been developed. One-pot formation of 5-(triazinyloxy)oxazoles using carboxylic acids, amino acids and a dehydrative condensing reagent, DMT-MM, followed by Ni-catalyzed Suzuki–Miyaura coupling with boronic acids provided the corresponding 2,4,5-trisubstituted oxazoles in good yields.
Keywords: one-pot oxazole synthesis; Suzuki–Miyaura coupling; triazine; 5-(triazinyloxy)oxazole; trisubstituted oxazole